Kazakhstan’s chairmanship in the CFM OIC in 2011 and the current problems in the Arab-Islamic world - Aktaulova, B. Zh. (Journal of Oriental Studies, 2016)
The author is dealing with the actual problems of the member states of the Organization of Islamic Cooperation in the context of Arab revolutions. The reasons and the consequences of the events of the «Arab spring» were analyzed. The author made an attempt to estimate the executed actions of Kazakhstan as the chairman of OIC.